Sociodemographic, Clinical and Crime-Related Actions’ Characteristics in Patients with Psychotic Symptoms which Evaluated with the Claim of Committing a Crime-Related Action in a University Hospital between 2012-2018 - Yıldız, Abdulkadir; Kılıç, Faruk; Çabuk, Selin; Aktaş Çallıoğlu, Gizem Çağla (The Bulletin of Legal Medicine, 2020)
Objective:The aim of the study is to determine sociodemographic, clinical and crime-related actions’ characteristics in patients with psychotic symptoms and to explore the effects of these characteristics on their criminal behavior and criminal responsibility. Materials and Methods:The 597 Forensic Medicine Board Reports prepared for assessment of criminal responsibility between 2012 and 2018 were investigated retrospectively.The reports and patient files of 182 individuals diagnosed by psychotic symptoms were examined in detail. Results: 85.7% of the cases were male.The mean age at the time of the crime was 40.87±11.78. 78.6% did not have a profession and did not work, mean duration of education was 7.98±3.19 years, 72% were single, divorced or separated, the mean disease duration of cases was 10.49±7.98 years, 22.5% had a comorbid psychiatric disorder and 14.6% of comorbid diseases were substance use disorder.Persecutory delusion was the most common delusion with a rate of 45%. 44.5% had a crime-related action history, 77.5% had committed a violent crime-related actions and most of the crime victims were familiar individuals of the patients. 67% did not have criminal responsibility, 12.1% had diminished criminal responsibility and 11.5% had criminal responsibility. Conclusion:In the evaluation of criminal responsibility, sociodemographic, clinical and crime-related actions’ characteristics should be considered in a holistic approach. Determining the risk factors in terms of criminal activities will help us to understand the reasons for the patients to take such actions and will guide the studies in terms of mental health and forensic psychiatry in cases with psychotic symptoms evaluated for criminal responsibility.